2010
DOI: 10.1111/j.1751-1097.2009.00654.x
|View full text |Cite
|
Sign up to set email alerts
|

Reaction Pathways for the Photodegradation of the Organophosphorus Cyanophos in Aqueous Solutions

Abstract: Photodegradation in aqueous solutions is an important pathway for many agrochemicals such as pesticides. In the present work, the photochemical transformation of cyanophos (CYA) was investigated in aqueous solutions using UV light within the 254-313 nm range as well as solar light. The study was performed in order to have a deep insight into the mechanistic pathways for the photochemical disappearance of CYA. Upon UV irradiation of an aerated solution of CYA, the degradation quantum yield was found equal to 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…An M+16 nucleoside oxidation product was formed from the photosensitizing dG 1 Py moiety in which the cyclohexenyl ring opened with a carbonyl group at the rupture site. 18 O labeling studies showed that the oxygen atom originated from H 2 18 O and not from 18 O 2 .…”
Section: Cells) and Llbc37 (Lymphoblastoid Cells) And Tumor Destructimentioning
confidence: 99%
“…An M+16 nucleoside oxidation product was formed from the photosensitizing dG 1 Py moiety in which the cyclohexenyl ring opened with a carbonyl group at the rupture site. 18 O labeling studies showed that the oxygen atom originated from H 2 18 O and not from 18 O 2 .…”
Section: Cells) and Llbc37 (Lymphoblastoid Cells) And Tumor Destructimentioning
confidence: 99%
“…In recent years, particular scientific interest has been focused on the pesticide nonpoint source (NPS) pollution associated to the water environmental safety. The increasing use of pesticides and other man-made chemicals represents the primary cause of contamination of soils, ground, and surface waters (Liebezeit et al, 2011;Matula, 2009Matula, , 2011Menager et al, 2010). These compounds show a relatively high persistence, widespread and rapid dispersion, and they may cause serious health and ecoenvironmental problems.…”
Section: Introductionmentioning
confidence: 99%
“…The T 1 absorption of cyanophos at 400 nm after the end of a pulse decayed to form a long-lived species appearing after 10 μsec, which was supposed to be the protonated amide intermediate from the product analysis. 42) The benzyl radicals formed via the homolytic cleavage of the C-S bond were detected in 20% aqueous acetonitrile for ethiofencarb and thiobencarb after pulse end. 35) Long-lived species insensitive to oxygen successively appeared at 320 nm and might be assigned from the product analysis to the corresponding carbanion (ethiofencarb) and carbocation (thiobencarb) via heterolytic cleavage of the C-S bond.…”
Section: Steady-state Photolysismentioning
confidence: 99%
“…125) The involvement of S* has been proposed for cyanophos, 42) and the weakening of the P-O-aryl bond by excitation may account for this reaction, as theoretically estimated for fenitrothion. 21) In the case of coumaphos upon exposure to UV light at 334 nm, either dimerization at the C 3 -C 4 position of the coumarin moiety or oxidative ring cleavage was the main reaction instead of ester hydrolysis.…”
Section: Organophosphorus (Op) Estersmentioning
confidence: 99%
See 1 more Smart Citation